Catalytic ozone decomposition and adsorptive VOCs removal in bimetallic metal-organic frameworks - Dong, Chen; Yang, Jia-Jia; Xie, Lin-Hua; Cui, Ganglong; Fang, Wei-Hai; Li, Jian-Rong (Nature communications, 2022)
Atmospheric ozone has long been a threat to human health, however, rational design of high-performance O 3 -decomposition catalysts remains challenging. Herein, we demonstrate the great potential of a series of isomorphous bimetallic MOFs denoted as PCN-250(Fe 2 M) (M = Co 2+ , Ni 2+ , Mn 2+ ) in catalytic O 3 decomposition. Particularly, PCN-250(Fe 2 Co) showed 100% O 3 removal efficiency for a continuous air flow containing 1 ppm O 3 over a wide humidity range (0 ‒ 80% RH) at room temperature. Mechanism studies suggested that the high catalytic performance originated from the introduction of open Co(II) sites as well as its porous structure. Additionally, at low pressures around 10 Pa, PCN-250(Fe 2 Co) exhibited high adsorption capacities (89 ‒ 241 mg g −1 ) for most VOCs, which are not only a class of hazardous air pollutants but also the precursor of O 3 . This work opens up a new avenue to develop advanced air purification materials for O 3 and VOCs removal in one. Warm-season O 3 pollution has been increasingly frequent worldwide in the past few years, exposing a threat to human health as well as the natural environment. Here, the authors showcase a stable MOF which can not only effectively capture various airborne VOCs, but decompose trace O 3 in ambient air.